The Role of Membrane Sweeping in Induction of Labor - Ayşe Günay (Medical Network, 2006)
OBJECTIVE: To determine the effect of the membrane sweeping (stripping) in labor induction and outcome of labour. STUDY DESIGN: The outcomes of labour induction (induction-delivery duration and mode of delivery) in term (38-42 weeks) pregnant women who swept or not swept at the onset of oxytocin induction. RESULTS: Sweeping the membranes have no significant effect on induction-delivery duration and mode of delivery in oxytocin induced term pregnant patients. CONCLUSION: There were no statistically differences in the outcome measures (induction-delivery duration and mode of delivery ) in multiparous and parous women at 38-42 weeks of gestation. No harmful side effects were noted according to the procedure.